The spread of Ebola: How the world health organization’s rhetoric contributed to virus transmission - Celeste Condit (Mètode Science Studies Journal: Annual Review, 2016)
The tragedy of the 2014 Ebola epidemic in West Africa was exacerbated by World Health Organization (WHO) rhetoric that depicted medical personnel as saviors of an irrational and emotional public. That common rhetoric rests on a faulty image of scientific knowledge as a substance that binds its affiliates into a community with special powers and immunities. This analysis shows how such rhetoric blinded the international community to attending to the potential role of health care sites and health care workers as vectors of disease transmission. This case illustrates why analysis of rhetoric is part of a full scientific approach to gaining, sharing, and deploying knowledge.